Answer:
For the equation -2x + y = 6,
the y - intercept = 6 and the x - intercept = -3
Step-by-step explanation:
x -Intercept is a point in the equation, where y coordinate is 0.
Similarly, y -Intercept is a point in the equation, where x coordinate is 0.
here, -2x + y = 6 is the given equation.
For y - intercept : put x = 0
we get -2(0) + y = 6
or, y = 6
⇒The y - intercept = 6
For x - intercept : put y = 0
we get -2x + 0 = 6
or, x = -6/2 = -3
⇒The x - intercept = -3
Hence, for the equation -2x + y = 6, the y - intercept = 6 and the x - intercept = -3